Hole selection by nesting swifts in medieval city-walls of central Spain - Corrales, Luis; Bautista-Sopelana, Luis M.; Santamaría, Tomás; Mas, Pedro (Ardeola, 2013)
Ardeola 60(2):291-304. 2013 Disturbance and predation risks from terrestrial animals decline the higher up the nest sites selected by birds that nest in wall cavities are located. Terrestrial predators can also negate the protective quality of higher nesting sites by approaching from above in walls. It is unknown how terrestrial predation risks from below and above walls determine nest site selection in cavity-nesting species. In relation to this situation, we describe nest-site selection in common swifts Apus apus in the medieval city walls of Ávila, Spain. We recorded the entry size, hole depth and the horizontal and vertical positions of cavities. Most cavities were empty despite their size being suitable for nesting. Swifts nested in cavities at least 12 cm deep and with an entry between 3.5 cm and 13 cm wide. Nests were 3.5 m above the ground and 1.7 m below the top of the wall, although there were suitable cavities at the lower and higher extremes, respectively. Higher predation risks and disturbances could explain why suitable cavities were empty at lower and higher heights. The distances to the ground and to the top of the wall, as well as the distance to the nearest corner, accounted for about one-tenth of the probability that a cavity was used for nesting. Our data do not indicate a possible reason for nesting near corners, but weather is an obvious candidate. Peer reviewed